REALITAS SOSIAL DALAM NOVEL MERINDU CAHAYA DE AMSTEL KARYA ARUMI EKOWATI - Fatimah Nur Janah; Amirudin Rahim; Haerun Ana (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to describe the social reality in the novel Merindu Cahaya de Amstel by Arumi Ekowati. This study is a type of library research. The data collection techniques used are reading techniques and note-taking techniques. The data in this study were analyzed using a sociology of literature approach. Based on the results of the study in the novel Merindu Cahaya de Amstel by Arumi Ekowati and the conclusion there is a social reality about family disorganization, the existence of family relationship breakdowns and its impact on individuals in building identity and facing social life, social reality about culture oriented towards diaspora and cultural identity, multicultural interaction, cultural heritage and cultural preservation, social reality about religion oriented towards spiritual journey, challenges in practicing Islamic teachings, and how a convert struggles to maintain his faith, social reality about education oriented towards access, support, and academic dynamics in the education system, social reality about the economy oriented towards survival strategies and individual financial independence in facing economic challenges, social reality about the problems of the younger generation in modern society oriented towards independence, challenges in finding work, economic struggles, to the search for the meaning of life, and social reality about violations of community norms on awareness of human rights, protection of women, and individual struggles to uphold justice in the face of acts of violence or coercion.